Comunicación asertiva y desempeño laboral de la enfermera. Hospital Leoncio Prado de Huamachuco 2018 - Arana Valderrama, Jhuliza Yubicxa (2019)
The present study is of descriptive correlational type, of cross section with quantitative approach, with the purpose of determining if there is a relation between the assertive communication and the work performance of the nurse in the Leoncio Prado Hospital of Huamachuco. The sample universe was constituted by 50 nurses to whom the instruments were applied: Assertive communication scale developed by Pradelli & Esqueda (1996) and the Scale of evaluation of work performance, elaborated by Soria (2016). The processed results are represented and interpreted in single and double entry tables. For the statistical analysis, the criterion independence test (chicuadrado) was used, reaching the following conclusions: the 58 percent of the nurses presented a high assertive communication level, the regular 34 percent and a low 8 percent. In the work performance, 52 percent of nurses has a high level, 36 percent in the regular level and 12 percent in the low level, there being a significant relationship between the level of assertive communication and work performance. (p <0.05).